Peningkatan Pengetahuan dan Keterampilan Usaha Dapoer Tiga Putri dalam Olahan Frozen Food melalui Konseling dan Training - Wellyalina Wellyalina; Abdi Abdi; Wenny Surya Murtius; Eli Ratni; Reni Koja (Warta Pengabdian Andalas, 2023)
The main problem partner’s face is the addition of processed materials to achieve the nutritional adequacy that the body needs, especially during this Covid-19 pandemic. Further, the types and packaging techniques used today are still in the form of plastic packaging available in plastic stores in general. The producer should have addressed the suitability of the type of plastic with the quality of the product being marketed and the type of packaging unsuitable for frozen food. Hence, the product quality quickly declined, but rather than that, the market expansion has yet to be achieved optimally. The method of activity consisted of brainstorming, discussion, and delivery of material about knowledge in frozen food processing, such as the addition of natural ingredients that can add nutritional value, packaging techniques suitable for frozen food as well as business licensing procedures from P-IRT, BPOM, and halal certificates. The activity showed an increase in the knowledge and skills of the Dapoer Tiga Putri business owners in processing frozen food, packaging techniques for frozen food using a vacuum sealer, and interest in managing business permits.